Oncological Outcomes of Nipple-Sparing Mastectomy in an Unselected Population Evaluated in a Single Center - Francisco Pimentel Cavalcante; Mirella Macedo Parente Araújo; Igor Moreira Veras; Ruffo Freitas Junior (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective Nipple-sparing mastectomy (NSM) has been traditionally used in selected cases with tumor-to-nipple distance > 2 cm and negative frozen section of the base of the nipple. Recommending NSM in unselected populations remains controversial. The present study evaluated the oncological outcomes of patients submitted to NSM in an unselected population seen at a single center. Methods This retrospective cohort study included unselected patients with invasive carcinoma or ductal carcinoma in situ (DCIS) who underwent NSM in 2010 to 2020. The endpoints were locoregional recurrence, disease-free survival (DFS), and overall survival (OS), irrespective of tumor size or tumor-to-nipple distance. Results Seventy-six patients (mean age 46.1 years) (58 invasive carcinomas/18 DCIS) were included. The most invasive carcinomas were hormone-positive (60%) (HER2 overexpression: 24%; triple-negative: 16%), while 39% of DCIS were high-grade. Invasive carcinomas were T2 in 66% of cases, with axillary metastases in 38%. Surgical margins were all negative. All patients with invasive carcinoma received systemic treatment and 38% underwent radiotherapy. After a mean of 34.8 months, 3 patients with invasive carcinoma (5.1%) and 1 with DCIS (5.5%) had local recurrence. Two patients had distant metastasis and died during follow-up. The 5-year OS and DFS rates for invasive carcinoma were 98% and 83%, respectively. Conclusion In unselected cases, the 5-year oncological outcomes following NSM were found to be acceptable and comparable to previous reports. Further studies are required.